Epidemiology of Pediatric Surgical Conditions Observed in a First-Level Hospital in Burundi - Gortan, Marianna; Caravaggi, Paola; Brooks, Giulia; Butoyi, Jean Marie Vianney; Bambara, Sylvestre; Nkurunziza, Joel; Mulemangabo, Mimico; Nzeyimana, Gordien; Harakaneza, Protais; Nshimirimana, Mwajuma; Tognon, Costanza; Gamba, Piergiorgio; et al. (Frontiers in Pediatrics, 2021)
Background - Little is known about the surgical conditions affecting the pediatric population in low-income countries. In this article we describe the epidemiology of pediatric surgical diseases observed in Mutoyi hospital, a first-level hospital in Burundi. Methods and Findings - We retrospectively reviewed the records of all children (0-14 years) admitted to the Surgery ward from January 2017 to December 2017. We also reviewed the records of all the patients admitted to the Neonatology ward in 2017 and among them we selected the ones in which a surgical diagnosis was present. 528 children were admitted to the surgical ward during the study period. The most common conditions requiring hospitalization were abscesses (29.09%), fractures (13.59%), osteomyelitis (9.76%), burns (5.40%) and head injuries (4.36%). The average length of stay was 16 days. 56 newborns were admitted to the Neonatology ward for a surgical condition; 29% of them had an abscess. Conclusions -Conditions requiring surgical care are frequent in Burundian children and have a completely different spectrum from the western ones. This is due on one side to an under-diagnosis of certain conditions caused by the lack of diagnostic tools and on the other to the living conditions of the population. This difference should lead to intervention plans tailored on the actual necessities of the country and not on the western ones.